TEMPORAL INSIGHTS: ASSESSING THE GROWTH PERFORMANCE OF RICE IN INDIA - DEVEGOWDA S.R, (The Journal of Research ANGRAU, 2024)
The study analyzed the growth, decomposition and instability of rice with regard to parameters such as area, production and yield bewtween 1970-’71 and 2019-’20 through the utilization of time series data. The findings indicated a notable expansion in the cultivation area of rice over the decades, except during the periods of 1980-’90 and 2010-’20. There was a declining trend in the area during the 2000-’10 decade. Production displayed a substantial increase throughout all decades and the overall study period. Yield demonstrated a minimal increase in the initial decade, followed by a substantial increase in all subsequent decades. The decomposition analysis revealed that the influence of the cultivation area on rice production was more prominent compared to the impact of yield during the studied time intervals. Yield’s influence was more pronounced during the 1970-’80 and 1990-’00 decades than in all other decades, while the interaction effect was relatively less significant. The stability of rice production was found to be the most precarious factor, followed by yield, with area exhibiting the least amount of instability. Policymakers need to prioritize research to boost rice yield, ensuring sustained production growth and implementing diversified cultivation strategies and resilient practices to counteract production instability.